Environmental policy making in highly contested contexts: the success of adaptive-collaborative approaches - Middle, Garry J (Curtin University, 2010)
This thesis examines the successes and failures of different approaches to environmental policy making in contexts where the level of conflict are significant, both in intensity and complexity. In this thesis the term policy making is used to cover three elements: the way that a policy is formulated, the decision making process to select the policy instruments, and the nature of the policy instruments used or proposed to be used. The research question here is “what policy making approach is most likely to succeed in highly contested contexts where levels of conflict are significant, both in intensity and complexity?” This research is built on the key proposition that some policy making approaches are, by their nature, better suited to highly contested contexts than others.The communicative/deliberative turn in planning was the starting theoretical framework for understanding how policy making can be carried out in highly contested contexts. It was argued that this framework has great value in understanding the processes involved in dealing with conflict, but that there are shortcomings. In particular, conflict is seen largely as a social problem, but conflict in environmental policy making often involves so-called wicked problems, where the conflict is deeper, more complex and involving longer timeframes than most planning conflicts. This thesis constructs a framework that describes the nature of conflict, with three broad themes being defined: social, governance, and science and information. It is argued that conflict is most likely where the resources at the centre of the conflict are scarce.Three types of scarcity are identified — decreasing quantity of a resource, increasing demand on a resource, and reducing quality of a resource.Four broad policy making approaches are defined: * The traditional expert-driven approach — a highly centralised approach dominated by the expert regulators using predominately science-based technical and statutory policy mechanisms; * The ecological modern approach — a more participative but still largely sciencebased approach, favouring the use of either market-based or voluntary policy mechanisms; * The collaborative approach — a highly participative form of policy making that does not necessarily favour a particular type of policy mechanism; and * The adaptive–collaborative approach — a special case of collaborative policy making where adaptive management measures are adopted to deal with the uncertainty of the science and information.These four approaches are analysed for their likely capacity to be successful in contexts where conflict is significant, and it is proposed that the first two are unlikely to be successful, whereas the two collaborative approaches, especially the adaptive– collaborative approach, would be successful where all the types of conflict are present.A qualitative multiple case study methodology was adopted to address the research question and to test the finding of the literature review, focusing primarily on the policy making of Western Australian (WA) Environmental Protection Authority (EPA - the peak environmental agency in WA). A specific methodology to determine policy making success or failure (evaluation) has been developed and applied in this study, involving the use of four evaluation criteria.The review of policy making by the EPA showed that whilst its policy making in cases where conflict was low were successful, it failed in cases where conflict was significant. It was noted that in all cases the policy making approaches adopted were either traditional expert– driven or ecological modern and not either of the two collaborative approaches, which, it was noted, was consistent with the finding of the literature review and would explain the policy failures in cases where conflict was significant.It was argued that recent policy making of the EPA shows some promise in dealing with conflict. This was because it has developed its Environmental Protection Policies (EPPs) more collaboratively, involving an additional complementary policy: the EPP sets high level objectives and deals with specific non–negotiable issues; and the more prescriptive implementation policy contains the detailed policy and management measures that would achieve the objectives in the EPP. These are called concurrent–complementary policies.A key part of this thesis is an in–depth analysis of a particular policy making exercise (major case study) set in a context where the three elements of conflict were significant, and the three resource scarcity types were present. The case study was Cockburn Sound, a large marine embayment approximately 20 kms south of Perth. Two concurrent–complementary policies were developed, and it was shown that the policy making approach of the implementation policy was adaptive–collaborative, and it was evaluated as being successful on all the four criteria. It was also noted that the draft EPP was a traditional expert–driven policy approach (although with a much improved level of participation) and that, it was evaluated as being unsuccessful on two of the four criteria — performance effectiveness and political support.The thesis concludes with a discussion of the broader implications for environmental policy making that can be drawn from this work, notably: that five policy making scenarios can be identified based on the nature and extent of conflict present, and recommendations made as to which policy making approach should be applied in each scenario.